Response to Boric Acid and Light in the Number and Biomass of Potato Microtubers Cv. “Floresta” - Azofeifa-Bolaños, José Bernal (2017)
In order to understand the performance of Solanum tuberosum L. “Floresta” in producing microtubers, the effect of four concentrations of boric acid (6.2 mg l-1, 7.75 mg l-1, 9.3 mg l-1, and 10.85 mg l-1) under two conditions—1) 8 hour dark and 2) 16 hour light photoperiod and 8 hour dark—was evaluated under in vitro culture conditions. Full-strength Murashige and Skoog medium was used as a control. The data analysis for the number and biomass of microtubers were significant for the condition (p ≤ 0.05). Concerning the concentration of boric acid and the interaction between factors, a significant difference was obtained for biomass (p ≤ 0.05). In dark conditions, a greater number of microtubers was obtained, although the biomass was lower compared to the light conditions where the biomass was higher, and the number of microtubers was lower. A concentration of 9.3 mg l-1 of boric acid in both types of conditions was the best treatment to produce a greater number and more biomass of microtubers. The differences identified in this work with regards to the number and biomass of microtubers were probably the combined result of genotype and specific culture conditions. Even considering this, the use of lighting conditions is proposed to induce larger and greener microtubers.